A questionnaire for assessment of the burden posed by sensitive skin – a step forward to provide solid ground for an important concept. (29th November 2018) - Linder, M.D.
Abstract : Linked article: This is a commentary on L. Misery et al., pp. 2217–2223 in this issue. To view this article visithttps://doi.org/10.1111/jdv.15186